2018
DOI: 10.1007/s00264-018-4042-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes after the Sauvé-Kapandji procedure for distal radio-ulnar post-traumatic instability: a case-control comparison of three different operative methods of stabilization of the ulnar stump

Abstract: These findings suggest that proximal ulnar stump pain may be caused not by radial or dorsal deviation of the proximal ulnar stump but by other dynamic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 23 publications
1
14
0
5
Order By: Relevance
“…12 Tomori et al, 2018 also reported a significant improvement of pain post operatively in patients undergoing various modifications of Sauvé-Kapandji procedure. 10 In our study, we observed a 89.88 percentage improvement in VAS scores for wrist pain with a statistical significance of p<0.001 at 2 year follow up.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…12 Tomori et al, 2018 also reported a significant improvement of pain post operatively in patients undergoing various modifications of Sauvé-Kapandji procedure. 10 In our study, we observed a 89.88 percentage improvement in VAS scores for wrist pain with a statistical significance of p<0.001 at 2 year follow up.…”
Section: Discussionsupporting
confidence: 56%
“…The extensor carpi ulnaris tendon is usually used to suspend and stabilize the ulna shaft in the modified procedure. [8][9][10] Retaining the ulnar head may allow for more normal transmission of force through the wrist, which may make this the preferred procedure in patients with "highdemand" wrists. While the DRUJ is fused, forearm pronation and supination are maintained or even improved by pseudoarthrosis of the ulna.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of surgical modifications of the SK procedure have been labeled to ameliorate the complication of ulnar stump pain- and hypermobility [ 10 ]. However, while ossification of the pseudarthrosis produces a similar debilitating complication rate amounting in surgical revision, above mentioned surgical modifications do not seem to affect the occurrence rate ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] suggest keeping the gap narrow to prevent proximal ulnar stump hypermobility. Contrarily, several authors argue that a gap of up to 15 mm produces most favorable results [ 8 , 10 , 12 , 13 ] (see Table 1 ), and Zachee et al. [ 14 ] state that early postoperative mobilization of the wrist could prevent re-ossification of the gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation